Estimation of optimal land use allocation among small holder (A1) farmer households in Zimbabwe. A case study of Long Croft Farm, in Mazowe District - Mugabe, Douglas; Chipunza, Nyasha; Mupaso, Norman; Munyati, Vincent Tinashe; Makarudze, Fungai Violet (Canadian Center of Science and Education, 2016)
Full-text